Prevention of depression and suicidal behaviours in school - Santos, José Carlos Pereira dos (2015)
Background: Depressive symptoms in adolescence may be a predictor of increased risk for depression and suicidal behaviors in adulthood (Maughan et al., 2013), as well as for psychosocial and health problems (Thapar et al., 2012). Early detection of depression and prevention of suicidal behaviors in school settings are essential given the adolescents' high vulnerability. The Project +Contigo is a longitudinal research project based on a multilevel network intervention with a view to promoting mental health and well-being and preventing suicidal behaviors. Objectives: The Project +Contigo aims to prevent suicidal behaviors in adolescents from secondary schools by assessing the presence of depressive symptoms in a non-clinical population of adolescents before and after the intervention. Methods: Quantitative study, with a quasi-experimental design and a control group. The group was assessed in three moments: before (Phase 1), at the end (Phase 2), and six months after the intervention (Phase 3), using a questionnaire consisting of sociodemographic information and the Beck Depression Inventory (BDI-II), Portuguese version (Beck & Steer, 1987; Martins, 2000). The intervention takes place in the classroom, and topics such as adolescence, self-esteem, problem-solving skills, among others are addressed. It is based on group dynamics (role-play, socio-therapeutic games, etc.). The study was conducted during the academic year 2013/2014 in 13 Clusters of Schools in the Central region of Portugal. The sample (non-probabilistic, intentional) was comprised of 1188 students in the 7th to 10th grades, with a mean age of 13.24 years and mostly boys (51.17%). Data were statistically analyzed (SPSS, version 20) using descriptive and inferential statistics. All ethical procedures were followed. Results: Overall, 27.2% of adolescents had depressive symptoms, of whom 15.7% had moderate or severe symptoms (Phase 1). The mean depressive symptoms decreased from Phase 1 (10.19) to Phase 2 (8.76) and Phase 3 (9.20) in both boys and girls and in all grades. Ninth-graders had the highest scores. The end of a cycle, with more demand in terms of evaluations, the need to choose areas of study, a new education institution, and greater adequacy of the expectations may help to explain this difference. Higher prevalence of depressive symptoms was found in the age group of 13-14 years in both boys and girls. Girls showed more depressive symptoms. The older the students, the higher the levels of depression, particularly in girls and in students older than 14 years of age (Twenge & Nolen-Hoeksema, 2002; Van Beek et al., 2012). Discussion: This study assessed the impact of the intervention on depressive symptoms in the short- and medium-term (six months), with statistically significant results in the reduction of depressive symptoms. In addition, it has also proven to be effective in the early detection of adolescents at risk for depression. As it is considered a mental health indicator, special attention should be given to the prevalence of depressive symptoms in girls and 9th-graders, taking into account this group's vulnerability. These data demonstrate the need for further projects aimed at the early detection of depression and prevention of suicidal behaviors in school settings.